2004
DOI: 10.1038/sj.ijo.0802808
|View full text |Cite
|
Sign up to set email alerts
|

Genes, lifestyles and obesity

Abstract: OBJECTIVE: To review the role of genes and lifestyle factors, particularly dietary habits and physical activity patterns, in obesity risk as well as their potential interactions. DESIGN AND MEASUREMENTS: A descriptive report of a number of genes definitely ascribed or potentially implicated in excessive fat accumulation leading to obesity as assessed by different research approaches (Mendelian transmission, genetic animal models, epidemiological association/linkage studies and genome-wide scans). Also, the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
95
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 75 publications
1
95
0
10
Order By: Relevance
“…Although genetics plays a role in weight gain, it cannot independently explain the dramatic rise in obesity rates over the past several decades, which is mainly attributed to changes in dietary and physical activity patterns (2). In addition to obesity prevention strategies concerning physical activity promotion and nutritional advice, various pharmacological and surgical treatments have been proposed to treat the obese, but diet is still the basic therapeutic tool against obesity (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although genetics plays a role in weight gain, it cannot independently explain the dramatic rise in obesity rates over the past several decades, which is mainly attributed to changes in dietary and physical activity patterns (2). In addition to obesity prevention strategies concerning physical activity promotion and nutritional advice, various pharmacological and surgical treatments have been proposed to treat the obese, but diet is still the basic therapeutic tool against obesity (3).…”
Section: Introductionmentioning
confidence: 99%
“…Programs to prevent overweight and obesity in children and adolescents may start by identifying factors associated with overweight and obesity in a population to ensure targeted and efficient strategies. Studies have identified predictors of overweight and obesity, including heredity (Marti et al, 2004), lifestyle (Hernandez et al, 1999;Robertson et al, 1999;Hanley et al, 2000) and environmental factors (Ma, 2002). However, the results of these studies are limited primarily to a series of simple or bivariate relationships.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are large interindividual differences in this compensatory response to increased fat intake. Indeed, the stability of body weight and its associated regulatory processes are influenced by compensatory genetics-dependent metabolic and neuroendocrine mechanisms (Marti et al, 2004). …”
Section: Introductionmentioning
confidence: 99%